Far-infrared irradiation attenuates vessel contraction by activating SERCA2 through disruption of SERCA2 and PLN interaction - Yun-Jin Hwang; So-Young Park; Jung-Hyun Park; Du-Hyong Cho (PLoS ONE, 2025)
Vascular smooth muscle cells (VSMCs) plays an important role in maintaining vascular function by responding to various vasoactive stimuli within blood vessels. Far-infrared (FIR) rays has been shown to possess a variety of physiological effects including vasodilation, while the underlying molecular mechanism remains elusive. Here, we explored the molecular mechanism by which FIR irradiation suppresses vascular contraction using rat VSMCs and aortas. FIR irradiation enhanced the transport of intracellular Ca 2+ from the cytosol to the sarcoendoplasmic reticulum (SER) via activation of sarcoendoplasmic reticulum Ca 2+ -ATPase (SERCA), which accompanied a decrease in intracellular ATP levels. Pretreatment with thapsigargin (TG), a specific SERCA inhibitor, or knockdown of SERCA2 gene expression reversed FIR irradiation-induced translocation of Ca 2+ into the SER. Notably, FIR irradiation promoted the dissociation of SERCA2 and phospholamban (PLN), an endogenous SERCA inhibitor, without altering their total protein expression levels. The array of effects elicited by FIR irradiation was not observed under hyperthermic conditions (39°C). Moreover, FIR irradiation, but not hyperthermal condition, decreased the phosphorylation of myosin light chain (MLC) at Ser19, which was restored by pretreatment with TG or the knockdown of SERCA2 gene expression. FIR irradiation attenuated phenylephrine-induced vessel contraction in endothelium-deprived rat aortas. Consistent with the in vitro results, the reduction in MLC phosphorylation caused by FIR irradiation was reversed following pretreatment with TG in isolated aortas. Additionally, FIR irradiation increased blood flow in the carotid arteries of mice. Collectively, these results suggest that FIR irradiation activates SERCA2 by promoting its dissociation from PLN, independent of hyperthermic effects. This activation lowers cytosolic Ca²⁺ and ATP levels, reducing MLC phosphorylation and vascular smooth muscle contraction. These findings provide scientific evidence for the therapeutic potential of FIR therapy in the treatment and prevention of arterial narrowing conditions such as pathological vasospasm, and peripheral artery disease.